THE EXISTENCE OF MYCOBACTERIAL POPULATIONS: ECOLOGICAL ASPECTS 1 - R. A. Nuratinov; N. Kh. Mesrobyan (Туберкулез и болезни лёгких, 2014)
The data available in the literature and the results of the authors’ studies on some issues regarding the ecology of mycobacteria were analyzed. The heterogeneity of their qualitative and species spread in the environment, circulation in the animal and human body and the trophic chain of transmission of pathogenic Mycobacterium species from animals to humans, and conversely, were traced. The degree of their spread in the natural landscapes depends on soil-climatic conditions and vertical zones.